Textile and clothing supply chain management : use of planning-link in the strategic planning process - Hussain, Deedar (2011)
In the current business world setting, the strategic directions are important not only for individual entities in the chain, but the complete chain itself should be considered for analysis. This helps developing competitive advantages and retaining them. This article presents a methodology for analyzing a supply chain and describes how entities in the chain can be improved to materialize the available and potential opportunities. The use of Planning-Link for mapping the cause and effect relationship between existing status of the chain to the future or planned outputs is suggested here which makes the process of strategic planning easier and logical.